High temperature hydrogenation of Ti–V alloys: The effect of cycling and carbon monoxide on the bulk and surface properties. (21st January 2016) - Suwarno, S.; Solberg, J.K.; Krogh, B.; Raaen, S.; Yartys, V.A.
Abstract: In the present work, the high temperature (425–575 °C) hydrogen storage properties of Ti–V alloys have been studied, both at static conditions and in a flow of hydrogen gas. The selected isothermal temperature range is considered as an optimal condition for hydrogen sorption enhanced steam reforming. When hydrogenation and dehydrogenation were performed in pure hydrogen gas and in vacuum, a large reversible hydrogen capacity of 3.95 wt. % H was obtained, demonstrating completeness of the formation and decomposition of (Ti, V)-dihydrides. However, when cycling was performed in a flow of hydrogen gas, the reversible hydrogen capacity decreased to ∼2 wt. % H caused by the formation of stable lower (Ti, V)-hydrides. A further decrease in the reversible hydrogen storage capacity took place when pure hydrogen gas was replaced by a mixture of hydrogen and carbon monoxide CO. This decrease was caused by the formation of an oxygen rich layer on the surface of the alloy, which was partially blocking the hydrogen exchange between the surface and the bulk of the sample. Highlights: H storage properties of Ti90V10 and Ti80V20 alloys were studied. Potential application of (Ti, V) in hydrogen sorption enhanced steam reforming was considered. Ti–V hydrides retain their reversible H storage capacity during the cycling in the flow of pure H2 gas. The bulk and surface of Ti–V alloys were significantly altered after cycling in H2  + CO. Processing in H2  + CO leads to the formation of oxygen rich layers that reduces H capacity.